License Management System for Little One Eduworld - Razalli, Nurul Izzati Syazleen; Kasim, Shahreen (Applied Information Technology And Computer Science, 2025)
This project presents the development of a License Management System for Little One Eduworld, aimed at overcoming the inefficiencies of a manual, paper-based kindergarten licensing process. The system offers a web-based platform that enables online submission, document uploads, real-time application tracking, and streamlined communication between applicants, verification officers, and administrative staff. Developed using Laravel, Vue.js, Inertia.js, and Tailwind CSS, the system was built under the Agile methodology to allow iterative improvement through continuous stakeholder feedback. Key features include secure user authentication, automated notification delivery, and PDF report generation. Functional, security, and user acceptance testing confirmed the system’s effectiveness, reliability, and user-friendliness. Overall, the project successfully enhances operational efficiency, reduces processing delays, and supports MZR Global Sdn Bhd’s efforts in expanding its kindergarten network through digital transformation.